Diazepam alters brain 5-HT function in man: implications for the acute and chronic effects of benzodiazepines. - Nutt, D; Cowen, P (1987)
The effect of diazepam on brain 5-HT-mediated neuroendocrine responses was studied in healthy male volunteers. An acute dose of diazepam (15 mg) significantly attenuated the prolactin and growth hormone responses to intravenous L-tryptophan. After 3 weeks administration of diazepam (25 mg/d) these responses had returned to normal despite much higher plasma diazepam concentrations, suggesting that tolerance had occurred. A reduction in brain 5-HT function may underlie some of the acute therapeutic actions of benzodiazepines. It is possible that excessive 'rebound' 5-HT activity may contribute to the abstinence syndrome seen on benzodiazepine withdrawal.